Silk Film Embossing System. - Paquette, Mark. (2017)
Abstract: New tools are often required to facilitate new discoveries and test new methods. Commercial offerings can be prohibitively expensive and difficult to customize. The development of ad-hoc tools provides the most flexibility and provides an opportunity to modify and refine a technology. An embossing system was developed for silk film imprinting and stamping in order to facilitate and add versatility to the efforts involving micro- and nanoscale device manufacturing in biopolymers. This system features temperature controlled embossing surfaces, adjustable embossing pressures, and variable embossing times. The device can also be fitted with interchangeable temperature controlled embossing and stamping tools. The design, development, fabrication, applications, and future improvements are explored for the system. This device may facilitate new discoveries in the realm of biopolymer micro- and nanomanufacturing and may provide a path towards high volume production of silk film based technologies.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Fiorenzo Omenetto.; Committee: Mark Cronin-Golomb, and Hu Tao.; Keyword: Biomedical engineering.